Polyethylene Glycol/Pullulan-Based Carrier for Silymarin Delivery and Its Potential in Biomedical Applications - Iwaniec, Julia; Niziołek, Karina; Polanowski, Patryk; Słota, Dagmara; Kosińska, Edyta; Sadlik, Julia; Miernik, Krzysztof; Jampilek, Josef; Sobczak-Kupiec, Agnieszka (International journal of molecular sciences, 2024)
Restoring the structures and functions of tissues along with organs in human bodies is a topic gathering attention nowadays. These issues are widely discussed in the context of regenerative medicine. Excipients/delivery systems play a key role in this topic, guaranteeing a positive impact on the effectiveness of the drugs or therapeutic substances supplied. Advances in materials engineering, particularly in the development of hydrogel biomaterials, have influenced the idea of creating an innovative material that could serve as a carrier for active substances while ensuring biocompatibility and meeting all the stringent requirements imposed on medical materials. This work presents the preparation of a natural polymeric material based on pullulan modified with silymarin, which belongs to the group of flavonoids and derives from a plant called Silybum marianum. Under UV light, matrices with a previously prepared composition were crosslinked. Before proceeding to the next stage of the research, the purity of the composition of the matrices was checked using Fourier-transform infrared (FT-IR) spectroscopy. Incubation tests lasting 19 days were carried out using incubation fluids such as simulated body fluid (SBF), Ringer's solution, and artificial saliva. Changes in pH, electrolytic conductivity, and weight were observed and then used to determine the sorption capacity. During incubation, SBF proved to be the most stable fluid, with a pH level of 7.6-7.8. Sorption tests showed a high sorption capacity of samples incubated in both Ringer's solution and artificial saliva (approximately 350%) and SBF (approximately 300%). After incubation, the surface morphology was analyzed using an optical microscope for samples demonstrating the greatest changes over time. The active substance, silymarin, was released using a water bath, and then the antioxidant capacity was determined using the Folin-Ciocâlteu test. The tests carried out proved that the material produced is active and harmless, which was shown by the incubation analysis. The continuous release of the active ingredient increases the biological value of the biomaterial. The material requires further research, including a more detailed assessment of its balance; however, it demonstrates promising potential for further experiments.
Keywords: Polyethylene Glycols; nosiče léků; Drug Carriers; polyethylenglykoly; lidé; lékové transportní systémy; spektroskopie infračervená s Fourierovou transformací; Glucans; Spectroscopy, Fourier Transform Infrared; glukany; koncentrace vodíkových iontů; Hydrogen-Ion Concentration; silymarin; Drug Delivery Systems; Silymarin; Humans